Oxidative stress, lipid metabolism, and neurotransmission in freshwater snail (Pomacea patula) exposed to a water-accommodated fraction of crude oil - Olivares-Rubio, Hugo. F.; Salazar-Coria, Lucía; Vega-López, Armando (HIDROBIOLÓGICA, 2017)
Background. Crude oil is a super mixture of chemical compounds and is commonly found in aquatic environments. The tegogolo (Pomacea patula Baker, 1922) is a Mexican freshwater snail endemic to Lake Catemaco in Veracruz; currently, however, its distribution has expanded to many freshwater ecosystems that suffer the impact of crude oil spills and oil byproducts like fuels. Goals. To assess a series of biomarkers involved in oxidative stress, neurotransmission, and fatty acid metabolism in tegogolos exposed to the water-accommodated fraction (WAF) of Maya crude oil (MCO). Methods. Tegogolo specimens were exposed to WAF of MCO obtained from loads of 0.1, 1, 10 and 100 mg/L. We evaluated ROS ( O2-* and H2O2), oxidative stress (TBARS and RC=O), enzymes involved in antioxidant defense (SOD, CAT, and GPx), some enzymes involved in neurotransmission (AChE, GDA, and CbE activities), and biomarkers of fatty acids metabolism (fatty acids levels and AOX activity). Results. Clear biomarkers responses were observed only in some tissues. ROS were clearly higher than controls in the foot, head, and kidney; however, others biomarkers of oxidative stress remain statistically unchanged. SOD response was irregular with respect to controls and treatments. In contrast, CAT (foot) and GPx (foot and intestine) were the more active enzymes and their activities were higher than in controls. The responses of some enzymes involved in neurotransmission suggest that compensation mechanisms exist between AChE and GDA in the foot and head. Fatty acids metabolism increased with exposure to WAF; however, these types of biomarkers seem unsuitable for monitoring the toxic effects produced by WAF at low environmental concentrations. Conclusions. We can conclude that under the exposure conditions discussed herein, the tegogolos showed acclimation to WAF of Maya crude oil by complex mechanisms. Background. Crude oil is a super mixture of chemical compounds and is commonly found in aquatic environments. Thetegogolo (Pomacea patula Baker, 1922) is a Mexican freshwater snail endemic to Lake Catemaco in Veracruz; currently,however, its distribution has expanded to many freshwater ecosystems that suffer the impact of crude oil spills and oilbyproducts like fuels. Goals. To assess a series of biomarkers involved in oxidative stress, neurotransmission, and fatty acidmetabolism in tegogolos exposed to the water-accommodated fraction (WAF) of Maya crude oil (MCO). Methods. Tegogolospecimens were exposed to WAF of MCO obtained from loads of 0.1, 1, 10 and 100 mg/L. We evaluated ROS ( O2-* and H2O2),oxidative stress (TBARS and RC=O), enzymes involved in antioxidant defense (SOD, CAT, and GPx), some enzymes involvedin neurotransmission (AChE, GDA, and CbE activities), and biomarkers of fatty acids metabolism (fatty acids levels and AOXactivity). Results. Clear biomarkers responses were observed only in some tissues. ROS were clearly higher than controls inthe foot, head, and kidney; however, others biomarkers of oxidative stress remain statistically unchanged. SOD response wasirregular with respect to controls and treatments. In contrast, CAT (foot) and GPx (foot and intestine) were the more activeenzymes and their activities were higher than in controls. The responses of some enzymes involved in neurotransmission suggestthat compensation mechanisms exist between AChE and GDA in the foot and head. Fatty acids metabolism increasedwith exposure to WAF; however, these types of biomarkers seem unsuitable for monitoring the toxic effects produced by WAFat low environmental concentrations. Conclusions. We can conclude that under the exposure conditions discussed herein,the tegogolos showed acclimation to WAF of Maya crude oil by complex mechanisms.